The Performance of School Principals and Teachers in Science Learning Achievement - Tri Yuni Hendrowati; M. Badrun; Robia Astuti; Mega Lestari (Jurnal Penelitian Pendidikan IPA, 2025)
Learning achievement cannot be separated from the performance of teachers and school principals. The principal as an academic supervisor indirectly plays a role in learning achievement through managing teacher resources and teachers play a direct role in learning achievement. This research aims to determine the performance of teachers and the performance of school principals in terms of mathematics learning achievement. This research used a qualitative research design with research data collection using interview, observation and documentation techniques. Meanwhile, for data validity, technical triangulation and source triangulation were used. Data analysis began with data reduction, data presentation and ended with drawing conclusions. The results of this research found that there was teacher and principal performance in achieving mathematics learning. The teacher's performance in this case was as a learning resource, class manager, motivator and evaluator. Meanwhile, the principal's performance as an academic supervisor is carried out by forming a supervision team, determining schedules, supervision techniques and instruments, checking the completeness of the administration of learning tools and the suitability of the teaching modules prepared by the teacher. Apart from that, the principal holds meetings and individual meetings to find out and monitor the learning process, evaluate learning, and the problems faced by teachers. However, the principal has not carried out monitoring by visited classes and directly observed the learning process carried out by teachers and has not used instruments when supervising the learning process and evaluation. However, in realizing learning achievements, school principals carry out follow-up actions to increase teacher teaching competence through MGMP activities, workshops or training for teachers.